The Effect of Time on Apoptosis Changes Following Ischemia-Reperfusion in Isolated Heart of Rats - Dostar, Yusef; Gorjani, Alireza; Hashemi, Mehrdad; Rezapour Shahir, Rambod (Asian Pacific Journal of Cancer Biology, 2017)
Background and objective: To study the time-dependent effects of ischemia – reperfusion on myocardium cells. Methodology: Male SD rats (270-330gr) were randomly grouped in four groups of 10 in an experimental study. After anesthesia using pentobarbital sodium (50-60 IP-kg/mg) the rats’ hearts in the treatment groups were isolated immediately and connected to langendorff apparatus with krebs solution at 37ºC and a fixed pressure. During stabilization, 30m ischemia and 60, 90, and 120min reperfusion was carried out on the hearts. Hearts of the control group remained intact. Immunhistochemistry of apoptotic cells was performed using TUNEL POD Kit and positive TUNEL myocardium cells of each group, in five microscopic view fields, was counted. The results were represented as mean ± SD. Findings: Apoptotic cell counts in control group was 1±0.4, and this figure in the treatment groups T/60min, T/90min, and T/120min was 2.0±0.5, 3.0±0.3, and 6.0±0.3 respectively. Comparison between the treatment groups and control group was carried out using one-way ANOVA and the results showed no significant difference between the groups T/90min and T/120min and the groups T/60 and control (p>0.05). However, the differences between the groups T/120min and T/60min (p<0.001) and groups T/120min and T/90min (p<0.01) was significant. Conclusion: The study showed that ischemia-reperfusion time can be effective on apoptotic changes of myocardium cells of heart.